Fenomena Childfree Dalam Perspektif Masyarakat Batak - Feriel, Sembiring Amelia; Muary, Rholand (FISIP Universitas Malikussaleh, 2023)
The emergence of the child-free phenomenon in Indonesia where the community is still guided by existing cultural values, does not adhere to child-freedom in forming a family. People believe that the purpose of marriage is to give birth to the next generation of families, even the term